2019
DOI: 10.5812/archcid.79701
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites Associated with Opportunistic Coccidial Infections Among Immunocompromised Individuals in Central Iran: A Cross Sectional Study

Abstract: Background: Protozoa and helminthic parasites are the most common opportunistic parasites infections associated with the gastrointestinal tract in immunocompromised patients. Objectives: There have been very few studies addressing this issue in central Iran and our purpose was to determine the frequency of the intestinal parasitic infections (IPIs) in different groups of immunocompromised patients admitted to the referral hospitals in Isfahan, Iran. Methods: A cross-sectional study was performed on 204 immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Malaria co-infection with coccidian intestinal parasite was not significantly associated with any of the socio-demographic factors (age, sex, education, age group, and area of residence) (P value=>0.05). Other studies have reported similar findings [57][58].…”
Section: Malaria Co-infection With Hiv and Aids Virussupporting
confidence: 81%
“…Malaria co-infection with coccidian intestinal parasite was not significantly associated with any of the socio-demographic factors (age, sex, education, age group, and area of residence) (P value=>0.05). Other studies have reported similar findings [57][58].…”
Section: Malaria Co-infection With Hiv and Aids Virussupporting
confidence: 81%
“…Increased risk of exposure to opportunistic intestinal protozoa infection usually took place in urban or sub-urban areas where people have a low level of educational background and poverty is rampant that forced them to live closely. The tropical climate also contributes significantly to the potency of transmission (Desy & Pratiwi, 2016;Gandahusada, 2008;Izadi et al, 2019). Some of the opportunistic intestinal protozoans species that are often found and cause clinical symptoms are Cryptosporidium sp, Cyclospora cayetanensis, Cystoisospora belii (formerly known as Isospora belii), and Blastocystis hominis.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of cryptosporidiosis, it is reported that it infects children more often, especially children under 5 years (toddlers). Clinical manifestations of opportunistic intestinal protozoa range from asymptomatic/ mild to severe diarrhea, while if infection occurs in immunocompetent patients the clinical spectrum is usually mild and selflimiting (Al-Shamiri et al, 2010;Gandahusada, 2008;Izadi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%